Crystal structure of bis(μ2-di-n-butyldithiocarbamato-κ3S,S′:S;κ3S:S:S′)-hexacarbonyl-di-rhenium(I), C24H36N2O6Re2 - Heard, Peter *; Halcovitch, Nathan R.; Lee, See Mun *; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C24H36N2O6Re2, triclinic, P¯1 (no. 2), a=10.3013(2) Å, b=11.3471(2) Å, c=14.5967(3) Å, α=72.540(2)°, β=73.074(2)°, γ=85.369(2)°, V =1557.05(6) Å3, Z =2, Rgt(F)=0.0214, wRref(F2)=0.0466, T =100(2) K.